Effect of sex status and breed-type on performance of highly stressed calves - Brazle, F.K.; Blecha, Frank; Riley, Jack G.; McLaren, J.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Bull and steer calves of mixed breed type were shipped from Newport, Tennessee to Manhattan, Kansas. Bull calves were castrated on arrival at Manhattan. Calves were classified into four breed-types as follows: (1) black, polled, medium-frame, number one muscling; (2) white-faced, feather-necked, medium-frame, number one muscling; (3) black or red with white face, medium frame, number one muscling; and (4) large-frame, mixed-color calves. The calves were in transit for 24 hours. Calves purchased and transported as steers outgained those purchased as bulls and castrated upon feedlot arrival by 26 lbs during the receiving phase and by 13 lbs on pasture. Fewer steer calves died than castrated bulls (7.7% vs. 13.2%). Steer calves had higher BVD antibody titers than bulls. Medium-frame, number one muscled, white-faced calves had a higher mortality rate (18.4%) than the average of other breed types (7.4%). The large-frame, number one muscled, mixed-color calves had the highest total gain.
Keywords: Beef; Performance; Gain; Breed